Low-Carbon Development through International Specialization - Gregor Schwerhoff; Ottmar Edenhofer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
A major concern in climate negotiations is that decarbonization may signi cantly hurt the development process. This paper shows that international specialization can contribute to making environmental and economic objectives compatible. When carbon effi ciency di ffers between two trading partners, environmental policy a ffects production cost di fferentially, so that the comparative advantage in technology is endogenous. Under a global climate agreement, a universal carbon tax would shift the production of energy intensive goods towards carbon effi cient economies. Once emissions are correctly internalized, trade becomes unambiguously bene cial for the environment and allows pursuing both environmental objectives and fast economic growth. Even in the absence of a climate agreement, free trade provides the option of indirectly accessing carbon e fficient technology abroad. This improves the marginal rate of substitution between consumption and environmental quality and thus achieves emission reductions even without international cooperation.
Keywords: Q56; F18; H23; 330